Determinants of Exclusive Breastfeeding in Babies 0-6 Months in Medan Sunggal District - Rotua Marseline Sihite; Achmad Rifai; Tri Niswati Utami (Journal La Medihealtico, 2021)
Exclusive breastfeeding for 6 months is very important for both mother and baby. The number of mothers who exclusively breastfeed their babies is still low (<80%). Medan Sunggal Puskesmas, Medan Sunggal Subdistrict, has a low achievement of exclusive breastfeeding in 2018 at 49.3% and decreased in 2019, namely 45.6%. Many factors influence exclusive breastfeeding, namely predisposing factors, enabling factors and reinforing factors. The purpose of this study was to find the determinants of exclusive breastfeeding in infants aged 0-6 months in Medan Sunggal District. Population of 256 people. Samples using the Slovin formula obtained 156 people. Data collection using a questionnaire. Data were analyzed by univariate, bivariate and multivariate using multiple logistic regression tests at the 95% significance level. The results showed that statistically knowledge (0.016), attitude (0.016), maternal ability (<0.001), breastfeeding facilities (0.001), husband's support (0.004), and parental support (0.010) had a significant effect on exclusive breastfeeding. Trust, ability of health workers, support from friends and the role of cadres have no effect. The dominant factor influencing is the ability of mothers with the value of Exp (B) 30,233, meaning that mothers have good abilities tend to be 30,233 times the mother gives exclusive breastfeeding to babies than the ability is not good. The conclusion is that the determinants of exclusive breastfeeding are knowledge, attitudes, abilities of mothers, breastfeeding facilities, husband's support and parental support. It is recommended that the Medan Sunggal government to increase regular counseling and form a companion group to make exclusive breastfeeding successful through peer groups or groups of mothers who love babies.